Digital Business Models - Wirtz, Bernd W. (Springer, 2019)
The Internet economy is essentially characterized by its considerable dynamic and speed of change. The rapid digitalization of numerous areas of life has resulted in a shift towards today’s Information Society. Therefore, since the beginning of the twenty-first century, online businesses have profoundly and progressively gained an importance. Against this background, the growing intensity of competition and the shortening of innovation cycles management decisions have become ever more complex and difficult, especially for the area of business models. In recent years, the business model concept has become a popular tool in business practice because it can help to successfully analyse and handle these complexities. Despite the great practical importance of business model management in the digital area, the conceptual basis in the literature is not very comprehensive. Thus, it seems necessary to develop a stronger conceptual foundation in order to deduce helpful insights and practical guidance for managers of digital businesses. The present book aims at filling this gap and to provide a detailed overview of the business model concept in the digital world. In preparing this book, I received various kinds of support from the former and current employees and doctoral students of the Chair of Information and Communication Management at the German University of Administrative Science Speyer. I would like to particularly thank Mr. Paul F. Langer (M.Sc.), Mr. Jan C. Weyerer (M.Sc.), Isabell Balzer (M.A.), Mr. Steven Birkmeyer (M.Sc.), Mr. Florian W. Schmidt (M.Sc.) and Mr. Daniel Schmitt (MPA) for their dedication to this project. The scientific development of a subject area thrives through the critical analysis and discussion of concepts and content. Given this fact and the currently inchoate state of knowledge regarding digital business models, I am grateful for every comment or suggestion for improvement. Furthermore, lecturers who are interested in using graphics and lecture with materials from this book are welcome to contact the author.
Concepts, Models, and the Alphabet Case Study